2013
DOI: 10.1002/cbdv.201200401
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Factor 1 Inducers from the Bark of Eucommia ulmoides as Cytoprotective Agents

Abstract: The barks of Eucommia ulmoides (Eucommiae Cortex, Eucommiaceae) have been used as a traditional medicine in Korea, Japan, and China to treat hypertension, reinforce the muscles and bones, and recover the damaged liver and kidney functions. Among these traditional uses, to establish the recovery effects on the damaged organs on the basis of phytochemistry, the barks of E. ulmoides have been investigated to afford three known phenolic compounds, coniferaldehyde glucoside (1), bartsioside (2), and feretoside (3),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 23 publications
(10 reference statements)
0
17
0
Order By: Relevance
“…Acanthoside D is identical with liriodendrin which has been reported as one of major constituents of E. ulmoides (Deyama 1983;Feng et al 2007;Nam et al 2013). Thus we chose this plant to isolate acanthoside D (=liriodendrin).…”
Section: Resultsmentioning
confidence: 94%
“…Acanthoside D is identical with liriodendrin which has been reported as one of major constituents of E. ulmoides (Deyama 1983;Feng et al 2007;Nam et al 2013). Thus we chose this plant to isolate acanthoside D (=liriodendrin).…”
Section: Resultsmentioning
confidence: 94%
“…E1; available online at www.redjournal.com) isolated from bark of Eucommia ulmoides to identify induction of HSPs and HSF1, using L132 normal lung cells. CA glucoside induced the highest expression of HSPs and HSF1 expression among the compounds tested (17). The glucoside-free form of CA exhibited similar effects on the patterns of expression of HSF1 and HSPs in the glucoside form, and thus, the glucoside-free form of CA was used during our experiments ( Fig.…”
Section: Ca Increased Expression Of Hsf1 Protein Accompanied By Tranmentioning
confidence: 90%
“…E1; available online at www. redjournal.com) (17). Compounds were dissolved in dimethyl sulfoxide and diluted in cell culture medium.…”
Section: Methods and Materials Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…CA possesses five-fold higher anti-inflammatory activity than that of aspirin [ 9 ] as well as potent anti-platelet aggregation activity [ 8 ]. Our previous study revealed a new function of CA as a potent inducer of heat shock factor 1 (HSF1), which upregulates heat shock proteins (HSPs), including HSP27 and HSP70 [ 14 ]. HSPs protect cells from various stimuli, including oxidative stress, heat, and radiation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%